Emerging role of oncogenic long noncoding RNA as cancer biomarkers. Issue 5 (26th September 2022) - Aprile, Marianna; Costa, Valerio; Cimmino, Amelia; Calin, George Adrian
Abstract: The view of long noncoding RNAs as nonfunctional "garbage" has been definitely outdated by the large body of evidence indicating this class of ncRNAs as "golden junk", especially in precision oncology. Indeed, in light of their oncogenic role and the higher expression in multiple cancer types compared with paired adjacent tissues, the clinical interest for lncRNAs as diagnostic and/or prognostic biomarkers has been rapidly increasing. The emergence of large‐scale sequencing technologies, their subsequent diffusion even in small research and clinical centers, the technological advances for the detection of low‐copy lncRNAs in body fluids, coupled to the huge reduction of operating costs, have nowadays made possible to rapidly and comprehensively profile them in multiple tumors and large cohorts. In this review, we first summarize some relevant data about the oncogenic role of well‐studied lncRNAs having a clinical relevance. Then, we focus on the description of their potential use as diagnostic/prognostic biomarkers, including an updated overview about licensed patents or clinical trials on lncRNAs in oncology. Abstract :